“Gestación en mujeres menores de diecinueve años en el hospital i integrado I. P. S. S. moyobamba año 1,982-1,992” - Bazán Vargas, Kieffer Segundo (1994)
Retrospective study of 1381 births in under nineteen years old served in the Department of obstetrics and Gynecology of the Hospital I integrated I.P.S.S. Moyobamba between January 1982 and January of 1992, with an incidence of 20.1%. 97.9% of births occurred in patients over the age of 15. The 70.2% were unmarried and living together, received inadequate prenatal control the 70.7%. Single mothers and cohabiting more frequently had preterm birth. The 39.3% was classified high-risk obstetric upon entering the hospital. The high-risk obstetrical is significantly related to maternal age and complications of pregnancy (toxemia and preterm). The complications of the pregnancy and childbirth more frequent were anemia (68.5%), infections (TBC-ITU-EIP) (36.5%), toxemia (28.7%), suffering fetal acute (29.2%), abnormalities of the dynamic of the delivery (24.6%), childbirth premature (9.8%), disproportion fetus pelvic (9.) 7.%). .. The. frequency of the pair...